EFFECT OF INTERPHASE CHARACTERISTIC AND PROPERTY ON AXIAL MODULUS OF CARBON NANOTUBE BASED COMPOSITES (Journal of Mechanical Engineering, 2010)
In carbon nanotube (CNT) based composite, due to the small (micrometer) size of reinforcements a large amount of interphases is developed during the time of production. It is important to assess whether the interphase is responsible for the poor mechanical properties of CNT-reinforced composite. In this research, the effect of interphase property and characteristics on effective mechanical properties of CNT based composites is evaluated using a 3-D nanoscale representative volume element (RVE). The effect of both soft and stiff interphases on the Tensile Elastic Modulus (TEM) of nanocomposites is investigated using the Finite Element Method (FEM) for the case of both long and short CNTs. With the increase of thickness of stiff interphase, the stiffness of the composite increases significantly for both the short and long CNT cases. On the other hand the increase of thickness of soft interphase reduces the stiffness of the overall composite in a considerable amount.Key Words: Carbon nanotube; Interphase; Representative Volume Element; Finite Element method; TensileElastic Modulus.DOI: 10.3329/jme.v41i1.5358Journal of Mechanical Engineering, Vol. ME 41, No. 1, June 2010 15-24